A 2.7 V Aqueous Supercapacitor Using a Microemulsion Electrolyte. Issue 7 (3rd March 2021) - Hughson, Fraser R.; Borah, Rohan; Nann, Thomas
Abstract: The use of aqueous electrolytes in energy storage devices is traditionally limited by the voltage stability window of water at 1.23 V. Here, we present the use of a microemulsion based electrolyte which, although mostly water by mass, has a voltage stability window of up to 5 V. This allows the cost and safety benefits of aqueous electrolytes to finally be realised in high voltage systems. Supercapacitors constructed using this electrolyte were able to achieve and maintain a capacitance of ∼40 Fg −1 and an energy density of ∼40 Wh kg −1 with a Coulombic efficiency of 99 % for over 10, 000 cycles on activated carbon. Abstract : Pushing the limit : This work presents the first use of a microemulsion electrolyte in a supercapacitor. Microemulsions have the unique ability to extend the electrochemical window of water well beyond the thermodynamic limit of 1.23 V. This enables the creation one of the highest voltages ever achieved for an aqueous supercapacitor.